EXPERIMENTAL EVALUATION OF TIE BAR EFFECTS ON STRUCTURAL BEHAVIOR OF SUSPENDED SCAFFOLDING SYSTEMS - Sevim, Baris; Bekiroglu, Serkan; Arslan, Guray (HONG KONG INST STEEL CONSTRUCTION, 2017)
The collapse of scaffolds can bring about substantial damage and economic loss. In recent years, over hundreds of people died and an even greater number have been injured because of inadequate scaffolding system designs. In this study, the effects of truss height and number of tie bars on the structural behavior of suspended scaffolding systems were experimentally investigated. Three full-scale scaffolding systems with truss heights of 30, 45, and 60 cm were tested in the laboratory. Each system included a wooden floor, steel purlins and trusses. The number of steel tie bars connected to the systems was also varied. A load transmission system was placed in these experimental systems to distribute single loads to the center of a specific area in a step-by-step manner using a load jack. After each load increment, the displacement was measured by means of linear variable differential transducers placed at critical points of the wooden floor, purlins, and trusses. This test was repeated for all systems and under all system conditions. The test results revealed that displacement increased exponentially in scaffolds with truss heights of 30, 45, and 60 cm without tie bars. Under the same load, systems with truss heights of 60, 45, and 30 cm revealed displacements of 8.8, 12.1, and 23.3 cm, respectively. The results of this work demonstrate that the number of tie bars and truss height considerably affect the structural behavior of scaffolding systems. Our findings further suggest that a scaffolding system with 60 cm-high truss and two tie bars presents optimal safety and cost-savings.
Keywords: Laboratory model; Load-displacement curve; Load transmission platform; Suspended scaffolding system; Tie bar effects; Truss height; LOAD CAPACITIES; CONSTRUCTION; DESIGN; SAFETY; Construction & Building Technology; Engineering; Materials Science